2011
DOI: 10.1177/0961203311403640
|View full text |Cite
|
Sign up to set email alerts
|

Clinical expression and morbidity of systemic lupus erythematosus during a post-diagnostic 5-year follow-up: a male:female comparison

Abstract: The aim of this study was to analyse the prevalence of the most relevant clinical features of the diagnosis of systemic lupus erythematosus (SLE) in a sample of male patients with lupus as well as the incidence of the main causes of morbidity in a 5-year period after the diagnosis. A further aim of this study was to investigate the impact of gender on expression and morbidity of SLE. Data were collected from the medical records of 59 male and 535 female patients with SLE who were diagnosed at the hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
47
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 11 publications
14
47
4
4
Order By: Relevance
“…Thus, male gender has been proposed as a predictor for poor systemic outcomes but the exact etiology remains unclear. 5, 28, 29 …”
Section: Female Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
“…Thus, male gender has been proposed as a predictor for poor systemic outcomes but the exact etiology remains unclear. 5, 28, 29 …”
Section: Female Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
“…[1,2] Whereas SLE is more common in women than in men, male patients are thought to have more severe disease than females. [3] Over 5-year follow-up, Stefanidou et al [4] found that male sex might be a poor factor in SLE prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned Euro-Lupus study revealed that at the diagnosis of SLE men more frequently show serositis, but in the course of fully symptomatic disease they suffer from arthritis less frequently than women [2]. Other studies showed higher prevalence of kidney involvement and failure in men [18,19], as well as higher frequency of thromboembolic episodes [18]. Also the results of studies conducted outside Europe suggest that the manifestation of SLE is more severe in male patients [17].…”
Section: Discussion Demographic and Clinical Characteristicsmentioning
confidence: 97%